Combining isometric knee extension exercises with hip adduction or abduction does not increase quadriceps EMG activity - Hertel, J.; Earl, J. E.; Tsang, K. K. W.; Miller, S. J. (British Journal of Sports Medicine, 2004)
Objective: To determine if the combined isometric contractions of knee extension/hip adduction and knee extension/hip abduction will elicit a different quadriceps and gluteus medius electromyographic (EMG) pattern as compared to isometric contraction of a uniplanar knee extension exercise.